Detection and Phylogenetic Analysis of an Exotic Strain of Porcine Epidemic Diarrhea Virus and Its Effect on an Affected Herd Immunized Against the Endemic Strain in Thailand - Christopher James Stott; Patumporn Jermsutjarit; Pornchai Pornpanom; Hongyao Lin; Angkana Tantituvanont; Dachrit Nilubol (Animals)
Porcine epidemic diarrhea (PED) is caused by the PED virus, with genogroup 2 (G2), comprising G2a and G2b, being the primary contributors to outbreaks worldwide. In Thailand, G2a was the only virulent strain identified until the emergence of the first G2b strain in 2014, followed by additional G2b strains in 2015–2016, particularly those closely related to virulent strains from China. This led to increased awareness of more frequent and complex outbreaks. This study examined farms affected by G2a and G2b strains, both employing planned exposure of sows to intestines from G2a-affected piglets, a traditional practice in Thailand. The analysis focused on the milk and colostrum profiles of sows, including viral neutralization and ELISA methods, as well as histopathological assessments of piglet intestinal villi. Additionally, a novel G2b strain was sequenced for phylogenetic and protein structure analyses. The results revealed no significant differences in colostrum and milk profiles between the farms. However, piglets infected with G2b showed significantly more severe intestinal damage. A unique insertion in the protein structure of the novel G2b strain led to the identification of a new epitope and potential changes in viral properties. This study highlights the importance of monitoring emerging strains and provides valuable insights for enhancing preventive strategies and advancing phylogenetic research.